Glucose homeostasis, beta cell function, and insulin resistance in relation to vitamin D status after gestational diabetes mellitus. (10th April 2017) - Shaat, Nael; Ignell, Claes; Katsarou, Anastasia; Berntorp, Kerstin
Abstract: Introduction: We wanted to determine vitamin D status after gestational diabetes mellitus (GDM) and to evaluate whether levels of 25‐hydroxyvitamin D3 (25OHD3 ) are associated with beta cell function, insulin resistance or a diagnosis of diabetes after GDM. Material and methods: Glucose homeostasis was assessed during a 75‐g oral glucose tolerance test one to two years after delivery in 376 women with previous GDM (287 European and 78 non‐European, including 33 Arab and 35 Asian women). Insulin resistance was estimated using homeostasis model assessment of insulin resistance (HOMA‐IR). The insulinogenic index (I/G30) and the disposition index [(I/G30)/HOMA‐IR] were used to calculate insulin secretion. Concentrations of serum 25OHD3 were determined. Results: Mean (±SD) 25OHD3 concentration was 50.0 ± 22.3 nmol/L and differed significantly among subgroups of body mass index, ethnicity, and glucose tolerance status; 53% had 25OHD3 levels <50 nmol/L and 87% had 25OHD3 levels <75 nmol/L. There was a negative correlation between 25OHD3 concentration and HOMA‐IR ( p  <   0.001) and a positive correlation between 25OHD3 and disposition index ( p  = 0.002) in univariable regression analysis. Correlations attenuated after adjustment for body mass index. In univariable regression analysis, 25OHD3 concentrations were significantly associated with diabetes after GDM ( p  = 0.004). However, in a multivariable model, non‐European origin, HOMA‐IR and insulinogenic index were significantly associated with postpartum diabetes, whereas 25OHD3 concentrations were not. Conclusion: Vitamin D deficiency/insufficiency in previous GDM cases appears to be associated with beta cell dysfunction and insulin resistance, but not with postpartum diabetes when factors well known to influence type‐2 diabetes were adjusted for.